Plan estratégico de la distribuidora Camel Cia. Ltda. de la ciudad de Loja, año 2012. - Rojas Vivanco, Andrea del Cisne (2012)
This work was developed with the aim of contributing to the administrative management of the company CAMEL with the aim of increasing its development, market share and become more competitive. CAMEL is a distributor, the experience acquired over the years as the distribution has enabled distribution solutions inspired by the needs and objectives of each company, thus becoming, in the first distributor in the middle. The research paper entitled "STRATEGIC PLAN CAMEL DISTRIBUIDORA CIA LTDA, LOJA CITY YEAR 2012" is focused on identifying some relevant aspects in the company so that they can provide alternative solutions to strengthen their image quality service and thus be more competitive in the market. For the development of the research was necessary to consider several objectives consisting in developing a strategic plan that allows better positioning in the market, it was necessary to conduct a situational analysis, SWOT analysis in order to know the state Current company also was made of high-impact matrix that allowed analyzing the key points, and determine the strategies that will help to solve the existing problems of the company. Note that for the fulfillment of those objectives were implemented methods and Regarding the methodology used for data collection methods were applied: scientific, inductive, deductive, analytical served as the basis for information processing, in terms of data collection, we used the following techniques: direct observation, interviews, surveys, and research instruments that gave a clearer picture of the reality of the company and organization . Among the results was applied one interview with the Manager, employee surveys and 306 customers, the information collected was tabulated, interpreted and analyzed, thus detecting certain opportunities and threats, as well as the strengths and weaknesses that have distributor. The discussion presents the situational analysis, SWOT analysis yielded information and identify: strengths, weaknesses, opportunities and threats of the company, by determining these internal and external factors was high impact matrix. With the contrast of these elements, was built strategies for improving internal and external aspects relevant and the organization. Finally there was a proposal based on a strategic plan to improve the operation and services of the company, the same implementation consisting of four strategic objectives, the total cost of this plan amounted to a total of $ 3,014.50 Finally it has come to the conclusion that the company provides quality service but the lack of a strategic plan could not get a better position in the market, which is why it is recommended to implement the Strategic Plan with the aim of solution to the problems that lead to sustainable development.